The Implementation of Inquiry Learning with Brainstorming Activity to Improve Intrinsic Motivation of Students of Grade XI MIA 4 SMA Negeri 1 Sragen - Chaerul Novitasari; Murni Ramli; Joko Ariyanto; Endang Sri Darmiyati (Universitas Sebelas Maret, 2015)
The research aims to improve students intrinsic motivation by applying the inquiry learning model combined with brainstorming activity on the excretory system in the grade 11 of MIA 4 SMA Negeri 1 Sragen 2014/2015. This research was a classroom action research consists of 3 cycles and takes place during March to April 2015. Data collected using observation, questionnaire and documentation. Data was validated using triangulation technique and analyzed using descriptive analysis. Shia (1998) stated, intrinsic motivation of students are measured through mapping observation the students activity to get good achievement and willingness of mastering the knowledge during the learning process. Other measurements is carried out by using self-assessment in the form of intrinsic motivation questionnaire which is directly filled by each student. The result Pre Cycle observation of intrinsic motivation show percentage score 55,47%. The target achievement percentage score of intrinsic motivation in research is 70%. The result shows that the learning model significantly increases students’ intrinsic motivation. The percentage of intrinsic motivation students in the for 3 cycles increased from 55.47% to 81.82% or increase points 26,28 %, in accordance with targets set.Keywords: inquiry learning, intrinsic motivation, biology, Senior High School.